Influence of surface microstructure on the sliding friction of plantar skin against hard substrates - Derler, S.; Huber, R.; Feuz, H.-P.; Hadad, M. (Wear, 2009)
This study investigated how the sliding friction coefficients of wet foot skin depend on the microscopic surface properties of contacted hard substrates. Fourteen subjects conducted repeated slip experiments with one foot on each of 28 different wet surfaces. The friction and normal forces transmitted to the substrates were measured using a tri-axial force plate, and coefficients of friction were determined over periods of stationary sliding. The surface structures of the substrates, characterised by an optical 3D profilometer, varied from roughness asperities in the range of micrometers to macroscopic surface elements in the range of millimetres. The analysis of the load dependence of the skin friction behaviour based on a two-term model provided information on the adhesion and deformation components of friction. Both adhesion and deformation were found to increase with the surface roughness of the substrates. Adhesion mechanisms seemed to predominate on smooth surfaces showing low friction coefficients (<0.3), while the contributions due to skin deformations were found to be up to 0.4 on rough surfaces with high friction coefficients (>0.5). Independent of friction measurements, the analysis of the surface microstructure of the substrates indicated that ploughing as a skin deformation mechanism could contribute around 50% to the deformation component of friction.